Application of multistage acid fracturing technology in deep carbonate thermal reservoirs. Issue 1 (1st October 2022) - Zhang, Zhiyong; Lv, Xiaolan; Ma, Feng; Wei, Kai; Li, Kai
Abstract : As the most common stimulation treatment in carbonate reservoirs, acid fracturing is also frequently used in carbonate geothermal wells, but it has not been applied in deep carbonate thermal reservoirs. The application of a multi-stage acid fracturing technology in Xiong'an deep carbonate thermal reservoir is introduced in this paper. The field application of technology has achieved a good stimulation effect. Multistage acid fracturing technology can effectively communicate the aquifer of carbonate thermal reservoir, improve the length of acid corrosion fracture, increase the conductivity of thermal reservoir and improve the water yield of a geothermal well. The technology is worthy to be popularized.